COMPARATIVE STUDY ON E-WASTE MANAGEMENT AND THE ROLE OF THE BASEL CONVENTION IN MALAYSIA, SINGAPORE, AND INDONESIA: A WAY FORWARD - Shad, Khalid Mehmood; Ling, Sarah Tan Yen; Karim, Mohammad Ershadul (Indonesia Law Review, 2020)
Electrical and electronic equipment waste (E-waste/WEEE) is a current global concern because of the increasing volume and improper treatment of e-waste. Generally, e-waste can be defined as discarded components of electrical and electronic equipment that have no reuse value. The improper disposal of e-waste can bring about catastrophic effects to mankind and the environment. The Basel Convention in 1992 categorizes e-waste as hazardous waste due to the presence of toxic materials. Currently, the production of e-waste is expanding at a considerable rate and is expected to reach 52.2 million tons globally by 2021. Singapore, Malaysia, and Indonesia are three neighboring countries that are facing the issue of e-waste management. The shortage of appropriate recovery and recycling facilities for formal e-waste treatment in the aforementioned three counties may lead to informal e-waste treatment or unsafe landfill, which cause harmful and hazardous effects to human lives and nature. This review provides a comprehensive overview of e-waste management from the perspective of Singapore, Malaysia, and Indonesia. Inadequate governmental policies, lack of e-waste laws, lack of public awareness, and lack of management strategies have caused various social and environmental issues. This work concludes with recommendations for the three countries to restrict the free flow of e-waste by establishing robust e-waste laws and improving the e-waste management system.